Investigating Women’s Representation and Identity in Tourism Context Using Narration: A Perspective from Bali - Praminatih, Gusti Ayu; Juwita Sari, Retno (Humanis, 2022)
The present study discussed the representation and identity of three selected women figures who contributed to the development of tourism in Bali and worked as a team leader, an entrepreneur, and an influencer, respectively. This study has two objectives: 1. to find out how women represent themselves and 2) to find out how women build their identity in the tourism context using narration. The authors used narrative inquiry to collect valuable stories from the informants. Using narrative inquiry, the stories produced by the informants were unique and meaningful. The study’s results revealed that women represented themselves as figures responsible for fulfilling domestic, i.e. family, and non-domestic roles, i.e. careers. The study also revealed that they still embraced traditional and domestic roles as their identity while simultaneously managing to actualise themselves in their careers. Keywords: identity, gender, narrative inquiry, women’s representation, women’s language